2004
DOI: 10.1159/000076134
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Serum Leptin Levels with Biochemical Markers of Bone Turnover and with Growth Factors in Normal Weight and Overweight Children

Abstract: Objective: To examine the hypothesis of an influence of leptin on growth factors and on biochemical markers of bone turnover of prepubertal overweight children. Design and Methods: 395 prepubertal children, 6–13 years of age, were selected and the relationships between circulating serum levels of leptin and insulin-like growth factor I (IGF-I), insulin growth factor binding protein-3 (IGFBP-3) and some biochemical markers of bone turnover (osteocalcin, OC; carboxyterminal propeptide of type I procollagen, PICP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 26 publications
4
19
1
4
Order By: Relevance
“…Furthermore, studies in children showed that normal weight children had significantly higher circulating osteocalcin levels than overweight children. 5,32 Osteocalcin levels have been reported to increase in overweight adults after weight loss. 8,9,30 The only existing human study with no increase in osteocalcin after weight loss was based on a high protein, high calcium diet, which probably explains this difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies in children showed that normal weight children had significantly higher circulating osteocalcin levels than overweight children. 5,32 Osteocalcin levels have been reported to increase in overweight adults after weight loss. 8,9,30 The only existing human study with no increase in osteocalcin after weight loss was based on a high protein, high calcium diet, which probably explains this difference.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking the gene that encodes osteocalcin (osteocalcin À/À) have an abnormal amount of visceral fat and exhibit glucose intolerance, IR and impaired insulin secretion compared with wild-type mice. 2 In humans, lower circulating osteocalcin levels were found in overweight 4,5 and diabetic subjects 6,7 compared with normal weight individuals. Moreover, osteocalcin concentrations increase after weight loss in overweight individuals 8,9 and after improvement in glycemic control in subjects with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Although a significant body of literature suggests that obesity reduces risk of osteopenia and osteoporosis (1, 2), there are also numerous recent reports that obesity and its comorbidities reduce bone formation (3–6). Obesity is accompanied by ectopic lipid deposition in multiple tissues, including the skeleton, where infiltration of adipocytes into the bone marrow niche may negatively impact bone formation (7, 8).…”
mentioning
confidence: 99%
“…Wpływ leptyny na wskaź-niki biochemiczne przemian kostnych u dzieci badany był również przez Bini i wsp. [9] u dzieci z nadwagą w wieku 6-13 lat. Dzieci otyłe miały wyższe stężenia leptyny, IGF-1, IGFBP-3 i niż-sze stężenie osteokalcyny niż dzieci o prawidłowej masie ciała.…”
Section: Dyskusjaunclassified